Vitex-2 Compact Identification of Candida Species Isolated from Urine Samples of Diabetic Patients in Rural Indonesian Community - Handayani, Lutfiana; Mujahid, Ikhsan (Proceedings Series on Health & Medical Sciences, 2025)
Diabetes mellitus (DM) increases the risk of fungal infections, particularly in the urine. The genus Candida is the most common cause of fungal infections in immunocompromised patients, including those with DM. The use of automatic identification tools such as Vitek-2 Compact allows for the rapid and accurate identification of Candida species. This study aims to identify the types of pathogenic fungi present in the urine of DM patients. This descriptive study used a cross-sectional design. Fungal examination were conducted macroscopically and microscopically on 15 urine samples from DM patients cultured on Sabouraud Dextrose Agar (SDA) media. Further identification was performed using the Vitek-2 Compact system to determine the species of fungi in positive samples. Culture results releaved that 12 out of 15 urine samples (80%) showed positive fungal growth. Identification using the Vitek-2 Compact system indicated a dominance of Candida species (66,7%), with Candida guilliermondii (33,3%) being the most frequently found species. Other fungal species identified included Candida krusei (16,7%), Candida famata (16,7%), Trichosporon asahii (16,7%), and Kodamaea ohmeri (16,7%). This study found a high prevalence of Candida infections in the urine of diabetic patients, with Candida guilliermondii being the most frequently identified species. The use of the Vitek-2 Compact system proved to be an effective method for the rapid and accurate identification of fungal species, highlighting its importance in clinical diagnostics. These findings emphasize the need for routine fungal screening in diabetic patients, as well as the importance of early and targeted antifungal therapy to prevent the complications associated with fungal infections, particularly in rural settings where healthcare resources may be limited.